Prognosis of new‐onset heart failure outpatients and collagen biomarkers. (14th July 2015) - Sanchis, Laura; Andrea, Rut; Falces, Carles; Llopis, Jaume; Morales‐Ruiz, Manuel; López‐Sobrino, Teresa; Pérez‐Villa, Félix; Sitges, Marta; Sabate, Manel; Brugada, Josep
Abstract Background Prognosis of heart failure patients has been defined in hospital‐based or retrospective studies. This study aimed to characterize prognosis of outpatients with new‐onset preserved or reduced ejection fraction heart failure; to explore the role of collagen turnover biomarkers (MMP2, MMP9, TIMP1) in predicting prognosis; and to analyse their relationship with echocardiographic parameters and final diagnosis. Methods This is an observational, prospective, longitudinal study. Outpatients with new‐onset heart failure symptoms referred to a one‐stop clinic were included. Echocardiography and biomarkers plasma levels determination were performed at the inclusion. A prospective follow‐up was conducted to report cardiovascular events. The discriminant analysis was applied to identify the parameters related to cardiovascular outcomes. Results A total of 172 patients (75 ± 9 years) were included, 67% with heart failure (64% preserved and 36% with reduced ejection fraction). During follow‐up (median 34·5 months), 32·6% had at least one cardiovascular event and 9·9% died. Heart failure groups showed no differences in cardiovascular outcomes with a higher rate of events than nonheart failure patients. MMP2 and TIMP1 were correlated with diastolic dysfunction (Rho 0·349 and 0·294, P < 0·001). In the discriminant analysis, the combination of biomarkers with clinical, biochemical and echocardiographic parameters was useful to predict cardiovascular outcomes (AUC ROC 0·806, Wilks lambda 0·7688, P < 0·001). Conclusions Prognosis of outpatients with new‐onset heart failure symptoms is comparable between heart failure with preserved or reduced subgroups. The addition of biomarkers specially MMP2 and high sensitive troponin I to other clinical, biochemical and echocardiographic variables can predict cardiovascular prognosis at the time of diagnosis.